The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.2337/diab.45.11.1605
|View full text |Cite
|
Sign up to set email alerts
|

The Pituitary-Gonadal Axis and Health in Elderly Men: A Study of Men Born in 1913

Abstract: The results of recent studies suggest that a relative hypogonadism in men is associated with several established risk factors for prevalent diseases. Therefore, we determined total and free testosterone, luteinizing hormone (LH), and sex-hormone binding globulin (SHBG) in a cohort of randomly selected men (n = 659) at 67 years of age. These data were analyzed cross-sectionally in relation to blood glucose and serum insulin, which were measured while fasting and after an oral glucose tolerance test, in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Diabetes was identified primarily by self-report [4548] with confirmation by additional testing or record review [45], or by FPG levels and medication use [4952]; several studies used 2-hour glucose levels as well [5357]. It is possible that this variety in definitions contributed to inconsistent associations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes was identified primarily by self-report [4548] with confirmation by additional testing or record review [45], or by FPG levels and medication use [4952]; several studies used 2-hour glucose levels as well [5357]. It is possible that this variety in definitions contributed to inconsistent associations.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies found an association between lower total T and incident diabetes [49, 55, 47, 58, 57], while 3 studies reported no association [46, 59, 48]. Two studies found an association between lower bioavailable or free T and incident diabetes [49, 57], while 3 studies reported no association [51, 46, 59]. One study examined total E2 and found an association [48], while another examined total and bioavailable E2 in men and diabetes and found no association [55].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study comprised two cohorts of men from Go Èteborg; both cohorts were population-based and in both the men were personally invited to participate. The cohort of men born in 1913 were randomly selected from the general population and has been extensively described elsewhere [13]. Altogether, 973 men were initially invited to a health screening examination in 1963, of whom 855 (88%) participated.…”
Section: Methodsmentioning
confidence: 99%
“…Low testosterone levels are associated with abdominal obesity and insulin resistance in men,39 and are an independent risk factor for developing T2D 40. Insulin sensitivity, visceral fat mass, blood pressure, and plasma lipids improve with testosterone substitution 41,42.…”
Section: Sex Differences In Hormonal Pathophysiologymentioning
confidence: 99%